Unpacking the policy processes for addressing systemic problems: The case of the technological innovation system of offshore wind in Germany - Kristin Reichardt; Karoline S. Rogge; Simona Negro (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
While empirical studies on technological innovation systems (TIS) usually focus on policy instruments and their suitability for curing identified weaknesses of such emerging systems, the underlying policy processes and their effects on these systems have been largely disregarded. We address this gap by exploring two crucial policy-making processes and their effects on the functioning and performance of the offshore wind TIS in Germany. Our findings indicate important positive and negative impacts of these processes on the TIS. For example, tardy reactiveness in policy action negatively influenced entrepreneurial activities, knowledge development and finally technology diffusion, whereas the incremental nature of the studied policy processes was necessary to improve TIS performance after it had been hampered by systemic problems. Based on our findings we derive policy implications and avenues for future research.
Keywords: 330